2006
DOI: 10.1523/jneurosci.2002-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Long-Range Coordination of Neural Activity during Gestalt Perception in Schizophrenia

Abstract: Recent theoretical and empirical research on schizophrenia converges on the notion that core aspects of the pathophysiology of the disorder may arise from a dysfunction in the coordination of distributed neural activity. Synchronization of neural responses in the ␤-band (15-30 Hz) and ␥-band range (30 -80 Hz) has been implicated as a possible neural substrate for dysfunctional coordination in schizophrenia. To test this hypothesis, we examined the electroencephalography (EEG) activity in 19 patients with a Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
306
3
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(336 citation statements)
references
References 47 publications
21
306
3
4
Order By: Relevance
“…Gamma activity has also been studied in schizophrenia using tasks with more complex processing demands. These studies have found schizophrenia patients to exhibit relatively lower frequency (Spencer et al, 2004) and decreased synchrony (Spencer et al, 2003) of an oscillation that is phase-locked to motor response in a Gestalt perception task, although others have found preserved gamma power in a different Gestalt perception task (Uhlhaas et al, 2006). Task demands with a stronger PFC-dependence have also revealed gamma deficits in schizophrenia patients, including impaired frontal gamma power (measured by magnetoencephalography) during mental arithmetic performance (Kissler et al, 2000) and an inability to mount increased delay-period gamma power in response to increasing working memory load during the N-Back (Basar-Eroglu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma activity has also been studied in schizophrenia using tasks with more complex processing demands. These studies have found schizophrenia patients to exhibit relatively lower frequency (Spencer et al, 2004) and decreased synchrony (Spencer et al, 2003) of an oscillation that is phase-locked to motor response in a Gestalt perception task, although others have found preserved gamma power in a different Gestalt perception task (Uhlhaas et al, 2006). Task demands with a stronger PFC-dependence have also revealed gamma deficits in schizophrenia patients, including impaired frontal gamma power (measured by magnetoencephalography) during mental arithmetic performance (Kissler et al, 2000) and an inability to mount increased delay-period gamma power in response to increasing working memory load during the N-Back (Basar-Eroglu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1 A and B) (12) and were analyzed for spectral power as well as for phase synchronization of induced oscillations. Mooney faces were chosen as stimuli because their perception is associated with increased synchronization of oscillatory activity in the beta and gamma band and with the coherent activation of extended functional networks (13,14). Therefore, we expected to find developmental changes in the topology of interareal synchronization and perhaps also in the frequency of the bands in which this synchronization occurs.…”
mentioning
confidence: 99%
“…Moreover, an association of neural oscillations with symptom dimensions has been demonstrated. Deficits in beta/gamma bands may contribute to perceptual impairments, and neural synchronization has been found correlated with positive and negative symptom dimensions of schizophrenia (Spencer et al, 2004;Uhlhaas et al, 2008;Uhlhaas et al, 2006). Changes in alpha synchronization during a memory task have been found to be correlated with task performance (Haenschel et al, 2010).…”
Section: Third Approach: Modulation Of Neural Oscillationsmentioning
confidence: 99%
“…Some investigations have found correlations of neural synchronization with memory performance and sensory processing, respectively (Spencer et al, 2004;Uhlhaas et al, 2008;Uhlhaas et al, 2006;Haenschel et al, 2010). Reduced synchronization, for instance, has been demonstrated in the anterior cingulate cortex (ACC) during an auditory discrimination task (Gallinat et al, 2002).…”
Section: Third Approach: Modulation Of Neural Oscillationsmentioning
confidence: 99%